PERGESERAN RESIPROSITAS MASYARAKAT DESA (STUDI ETNOGRAFI PERGESERAN NILAI TENTANG SUMBANGAN PERKAWINAN DI MASYARAKAT BRONGSONGAN, DESA SIDOREJO, KECAMATAN BENDOSARI, KABUPATEN SUKOHARJO) - Masithoh, Nuraeni Dewi; Wijaya, Mahendra; Kartono, Drajat Tri (Jurnal Analisa Sosiologi, 2013)
The aim of this research is (1) to find out how the shift of wedding contribution reciprocity is in Brongsongan society, Sidorejo Village, Bendosari, Sukoharjo Regency, and (2) to find out the cause of reciprocity shift in wedding contribution in Brongsongan society, Sidorejo Village, Bendosari, Sukoharjo Regency. This study was taken place in Brongsongan Village, Bendosari, Sukoharjo Regency. The research strategy employed was ethnography study, aiming to get an in-depth meaning of social-cultural activities interrelationship. The data was collected through direct observation and in-depth interview.The result of research showed that the shift of wedding contribution in Brongsongan society could be seen from: form, way of contributing and contribution function. Contributing was no longer a part of mechanic solidarity, but a part of organic solidarity and various transactional activity in the objective of getting either material or social benefit.Â Keywords: Reciprocity, Exchange, Wedding Contribution